Ajuste do modelo de Bell para estimativa de chuvas intensas para sete estações meteorológicas do Estado de Mato Grosso - Sousa, Isabela Lima Silva e (2014)
The intense rainfall is the main cause of disasters in Brazil. It is common the occurrence of floods of streets and homes, as well as the collapse of hills, that even kill people. In agricultural areas, intense rainfall promotes loss of soil and nutrients, which can reduce crop productivity and increase the price of agricultural products for the population. To alleviate the problems caused by the rainfall, it is necessary to perform studies of the distribution and intensity of precipitation that may occur in certain localities. Such studies serve as subsidies for the construction of urban and rural hydraulic structures to restrain the excess of surface runoff or to direct it to appropriate places. In this study, we set the parameters of the Bell model for seven meteorological stations in the state of Mato Grosso, Brazil, using specific pluviometric and pluviographic data of each station. Since rainfalls have irregular spatial and temporal distribution, an individualized study is required to provide reliability to hydraulics projects. The coefficients of the Bell model were adjusted and we estimated IDF equations based on the adjusted model. These equations were compared with standard equations estimated from the Analysis of Pluviograms. Considering all years of pluviographic data series, the Bell local model presented the best performance in four stations. By using data series of two years, the performance of Bell local model worsened, indicating that longer data series are required to increase the reliability of results.